Highly Sensitive Lead Ion Detection in One Drop of Human Whole Blood Using Impedance-Modulated Field-Effect Transistors and a Portable Measurement Device. (29th June 2020) - Wang, Shin-Li; Hsieh, Ching-Yen; Sukesan, Revathi; Chen, Jung-Chih; Wang, Yu-Lin
Abstract : This study reports the development of a rapid heavy metal ion screening tool for whole blood samples. The test system consists of an ion selective membrane-based impedance modulated field effect transistor (FET) sensor and a portable sensor measurement unit. This study focuses on the direct detection of lead ions in whole blood, without extensive sample pre-treatments. The sensing methodology is based on impedance changes in the membrane due to the specific ionophore-target metal ion interaction in the presence of a strong electric field. The changes in impedance caused by heavy metal ions are amplified by the FET to obtain a highly sensitive lead ion detection, with very low detection limit (near 10 −11 ∼ 10 −10 M Pb 2+ ). To reduce the complexity and enhance sensor performance, the whole blood samples are fractionated on chip without any external actuation/automation using simple gravitational blood cell separation. The test results in PBS, human serum and whole blood samples demonstrate high sensitivity and wide dynamic range of lead ion detection. The miniaturized extended gate FET sensor system is ideal for point of care and home-care diagnostics for heavy metal ion in blood.